Scandal - Hamilton, Cosmo, 1872?-1942; Culter, Richard, 1883-1929 (Salt Lake City, UT : Project Gutenberg, 2015)
"Scandal: A Novel" by Cosmo Hamilton is a fictional narrative written in the early 20th century. The story centers around Beatrix Vanderdyke, a wealthy and beautiful debutante navigating the complexities of high society in New York. Her relationships with a controversial portrait painter, Sutherland York, and the socially prominent Pelham Franklin set the stage for the unfolding drama of scandal and romance. The opening portion of the novel introduces Beatrix as she is spotted out and about with Sutherland York, provoking the curiosity and concern of her peers. This initial glimpse reveals Beatrix as a figure of beauty, privilege, and discontent, eager to assert her independence. As she interacts with York, whose seductive charm complicates her life further, the tension between societal expectation and personal desire becomes palpable. The conversations around her suggest a deeper conflict brewing, hinting at the potential for scandal that may well up from her unorthodox choices. (This is an automatically generated summary.)
Release date is 2015-10-26
Produced by Al Haines
Keywords: Love stories; Children of the rich -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Social life and customs -- 20th century -- Fiction